HUBUNGAN TINGKAT PENGETAHUAN DENGAN KESIAPAN DOSEN POLTEKKES KEMENKES TANJUNGPINANG DALAM MENGHADAPI INTERPROFESSIONAL EDUCATION (IPE): Relationship Between Knowledge and Readiness of Lecturers at Poltekkes of The Ministry of Health in Tanjungpinang about Interprofessional Education (IPE) - yuliyana, rian; Martias , indra; Pusparianda, Dewi (Poltekes Kemenkes Tanjungpinang, 2021)
Interprofessional Education was first initiated by the World Health Organization (WHO) as a strategy to increase collaboration between different health workers in order to see a problem and be able to solve it holistically so as to achieve quality health service outcomes. Poltekkes Kemenkes Tanjungpinang has conducted a workshop on IPE in 2018, besides that several lecturers have also been trained to become IPE facilitators by the PPSDM Health Ministry of the Republic of Indonesia. This study was aims Â to determine the relationship between the level of knowledge and the readiness of lecturers at the Poltekkes Kemenkes Tanjungpinang in facing Interprofessional Education (IPE). This research was a quantitative research, the type of research used is descriptive analytic which is analyzed by the chi square test and exact fisher. The subjects of this research were 42 lecturers of Tanjungpinang Health Poltekkes. The results Â was showed that the risk factors for lecturers who had sufficient knowledge tended to be 2,567 times more unprepared for IPE than those who had good knowledge. However, there was no significant relationship between the level of knowledge and the readiness of lecturers to face IPE. It is suggested that this research can be taken into consideration by policy makers at the Poltekkes Kemenkes Tanjungpinang in preparing Interprofessional Education (IPE) for both lecturers and students of the three study programs.